Cyclophosphamide plus etoposide is a safe and effective mobilization regimen in patients with multiple myeloma. (October 2021) - Heider, Michael; Grass, Sandra; Dill, Veronika; Rämisch, Stephanie; Winter, Christof; Verbeek, Mareike; Götze, Katharina S.; Bassermann, Florian; Jilg, Stefanie
Abstract: High-dose chemotherapy followed by autologous stem cell transplantation is a major component in the treatment of patients with multiple myeloma. As a prerequisite, the successful collection of a sufficient number of viable peripheral blood hematopoietic CD34+ cells is critical. A common standard protocol for mobilization is currently not defined and critically discussed especially in German-speaking Europe. In times of the Covid-19 pandemic, safe and effective strategies have to be chosen to minimize hospitalization times and severe courses. In this single-center retrospective analysis, safety and efficacy of cyclophosphamide plus etoposide (CE) and growth-factor support (n = 33) was compared to cyclophosphamide mono treatment and growth-factor support (n = 49) in 82 patients with multiple myeloma at first diagnosis. CE was superior to cyclophosphamide mono with a significantly higher number of collected CD34+ cells (15.46 × 10 6 CD34 + cells/kg vs. 9.92 × 10 6 CD34 + cells/kg), significantly faster engraftment of granulocytes after stem cell transplantation (day 10.5 vs. day 11.6), shorter duration of the inpatient stay (17.47 days vs. 19.16 days) and significantly less transfusions (8.82 % vs. 30.61 % patients receiving transfusions). The safety profile was comparable in both groups and in line with published data. We conclude that CE is a safe and highly effective mobilization protocol in patients with multiple myeloma at first diagnosis and appears to be superior to the commonly used cyclophosphamide mono regimen.